Consortium of Phosphorus-Solubilizing Bacteria Promotes Maize Growth and Changes the Microbial Community Composition of Rhizosphere Soil - Dan Luo; Ju Shi; Mei Li; Jixiang Chen; Tianfeng Wang; Qingfang Zhang; Linhai Yang; Ning Zhu; Yonggang Wang (Agronomy, 2024)
Phosphorus deficiency severely limits crop yields and hinders sustainable agricultural development. Phosphate-solubilizing bacteria (PSB) are beneficial for crop growth because they enhance the uptake and utilization of phosphorus. This study explored the phosphorus-solubilizing, IAA-producing, nitrogen-fixing, potassium-solubilizing, and siderophore-producing abilities of three bacterial strains (Pantoea sp. J-1, Burkholderia cepacia Z-7, and Acinetobacter baumannii B-6) screened from the maize rhizosphere. A pot experiment was also conducted to explore the role of screened PSB in the growth of maize. Finally, the effects of the PSB on the physicochemical properties, enzyme activities, and microbial community structure of maize rhizosphere soil were analyzed. The results showed that strain Z-7 had the strongest abilities phosphorus solubilization, nitrogen fixation, potassium solubilization, and siderophore production, while strain J-1 exhibited the highest yield of IAA. The application of PSB promoted the growth of maize plants to different extents. Among the different treatments, the mixed bacterial treatment (J-1 + Z-7 + B-6) had the most potent growth promotion effect, and the consortium treatment significantly enhanced the activity of soil phosphatase. Soil pH, total phosphorus (TP), total potassium (TK), available phosphorus (AP), NH4+-N, and NO3−-N are key factors for the growth of maize plants. In addition, PSB significantly altered the microbial community structure in the maize rhizosphere soil, and the relative abundance of Proteobacteria increased by 16.07–69.10% compared to the control. These PSB have obvious growth-promoting abilities, with the potential to enhance crop productivity as excellent candidate strains for the development of biological fertilizers.